Investigation of biodistribution and tissue penetration of PEGylated gold nanostars and their application for photothermal cancer treatment in tumor-bearing mice. Issue 1 (26th November 2019) - Chen, Chao-Cheng; Chang, Deng-Yuan; Li, Jia-Je; Chan, Hui-Wen; Chen, Jenn-Tzong; Chang, Chih-Hsien; Liu, Ren-Shyan; Chang, C. Allen; Chen, Chuan-Lin; Wang, Hsin-Ell
Abstract : PEGylated gold nanostars (pAuNSs) and their radioactive surrogate ( 111 In–DTPA–pAuNS), with unique physiochemical properties, are thought to be a promising agent for image-guided photothermal therapy (PTT). Abstract : Gold nanostars (AuNSs), with unique physicochemical properties, are thought to be a promising agent for photothermal therapy (PTT). In this study, we prepared PEGylated gold nanostars (pAuNSs) using the HEPES-reduction method. The high photothermal conversion efficiency (∼80%) and photothermal stability of pAuNSs were demonstrated in vitro and in vivo . 111 In–DTPA–pAuNSs were prepared as a radioactive surrogate for the biodistribution studies of pAuNSs. In both microSPECT/CT images and the biodistribution study, the tumor-to-muscle (T/M) ratio reached a maximum at 24 h post intravenous injection of 111 In–DTPA–pAuNSs. The high linear correlation between the 111 In radioactivity and the gold content in the tumors ( R 2 0.86–0.99) indicated that 111 In–DTPA–pAuNSs were appropriate for noninvasively tracking pAuNSs in vivo after systemic administration. Histological examination after silver enhancement staining clearly illustrated that the accumulated pAuNSs in the tumors were mainly located on the luminal surface of vessels. The mice bearing a SKOV-3 xenograft exhibited remarkable therapeutic efficacy with negligible organ damage after receiving pAuNS-mediated photothermal therapy. Our findings suggested that pAuNSs, together with their radioactive surrogate 111 In–DTPA–pAuNSs, are promising for applications in image-guided photothermal therapy.